Protective Effect of Melatonin on Acute Pancreatitis - Jolanta Jaworek; Joanna Szklarczyk; Andrzej K. Jaworek; Katarzyna Nawrot-Porąbka; Anna Leja-Szpak; Joanna Bonior; Michalina Kot (Hindawi Limited, 2012)
Melatonin, a product of the pineal gland, is released from the gut mucosa in response to food ingestion. Specific receptors for melatonin have been detected in many gastrointestinal tissues including the pancreas. Melatonin as well as its precursor, L-tryptophan, attenuates the severity of acute pancreatitis and protects the pancreatic tissue from the damage caused by acute inflammation. The beneficial effect of melatonin on acute pancreatitis, which has been reported in many experimental studies and supported by clinical observations, is related to: (1) enhancement of antioxidant defense of the pancreatic tissue, through direct scavenging of toxic radical oxygen (ROS) and nitrogen (RNS) species, (2) preservation of the activity of antioxidant enzymes; such as superoxide dismutase (SOD), catalase (CAT), or glutathione peroxidase (GPx), (3) the decline of pro-inflammatory cytokine tumor necrosis α (TNFα) production, accompanied by stimulation of an anti-inflammatory IL-10, (4) improvement of pancreatic blood flow and decrease of neutrophil infiltration, (5) reduction of apoptosis and necrosis in the inflamed pancreatic tissue, (6) increased production of chaperon protein (HSP60), and (7) promotion of regenerative process in the pancreas. Conclusion. Endogenous melatonin produced from L-tryptophan could be one of the native mechanisms protecting the pancreas from acute damage and accelerating regeneration of this gland. The beneficial effects of melatonin shown in experimental studies suggest that melatonin ought to be employed in the clinical trials as a supportive therapy in acute pancreatitis and could be used in people at high risk for acute pancreatitis to prevent the development of pancreatic inflammation.